Distúrbios neurológicos em trabalhadores com baixos níveis de chumbo no sangue. I: Neuropatia periférica - Cordeiro, Ricardo [UNESP]; Lima Filho, Euclydes C.; Salgado, Paulo E. T. (FapUNIFESP (SciELO), 1996)
This is a cross-sectional study with a randomized choice of individuals aiming at studying the validity of the Brazilian biological exposure limits applied to lead level in the blood (PbB) and delta-aminolevulinic acid in the urine (ALAU), which are 60 μg/dl and 10 mg/g.creat., respectively. For this purpose, twenty workers, whose PbB and ALAU values have been below these limits over the past two years, were selected at random at a battery production plant in the State of S. Paulo, Brazil. The workers were submitted to a peripheral nerve conduction study. The results were compared with those obtained for workers of a control group also chosen at random. The lead workers showed a decrease in the velocity conduction of the radial nerves. Comparing this group with a randomized control group, a significant difference was observed (p-value = 0.0067). The results suggest that the Brazilian biological exposure limits above should be rearranged.
Neurological disturbances in workers with low levels of lead in the blood. I: Peripheral neuropathy
Keywords: Lead poisoning, prevention; Occupational exposure, standard; Peripheral nervous system diseases, chemical induced; adult; blood; case control study; chemically induced disorder; clinical trial; controlled clinical trial; controlled study; human; lead poisoning; male; maximum allowable concentration; nerve conduction; occupational disease; pathophysiology; peripheral neuropathy; randomized controlled trial; Adult; Case-Control Studies; Humans; Lead Poisoning; Male; Maximum Allowable Concentration; Neural Conduction; Occupational Diseases; Peripheral Nervous System Diseases